Determinants of Life Expectancy in Malaysia - Siew Keen, Wong; Jerome Swee Hui, Kueh (RSIS International, 2025)
Life expectancy is regarded as a vital indicator of a nation's health, social progress, and economic development. This study analyzes the determinants affecting life expectancy in Malaysia, employing annual data on GDP per capita, inflation rate, mortality rate, and unemployment rate from 1990 to 2022. The re search employed the Augmented Dickey Fuller (ADF) unit root test, the Johansen and Juselius cointegration test, and the Vector Error Correction Model (VECM) to analyze the relationship between life expectancy and its determinants. The results demonstrate a long term equilibrium among the variables, revealing that GDP per capita positively influences life expectancy, whereas inflation, unemployment, and mortality exert negative effects. The Granger causality analysis within the VECM framework demonstrates unidirectional short run causal relationships: inflation and mortality rates affect GDP per capita, mortality influences inflation and unemployment, and life expectancy impacts unemployment. These findings underscore the interconnectedness of economic, demographic, and health determinants, providing essential insights for policymakers in developing integrated strategies to sustain improvements in population health and life expectancy in Malaysia.